Occupational and Return-To-Work Characteristics of Covid-19 Patients After Treated in Udayana University Hospital - Karya, I Kadek Jony Dwi; Wirawan, I Made Ady; Purnamasidhi, Cokorda Agung Wahyu; Florensia, Maria; Akatsu, Haruko (Institute of Topical Disease Universitas Airlangga, 2024)
Corona virus disease 2019 (COVID-19) is a new disease caused by severe acute respiratory syndrome corona virus 2 (SARS-COV-2). The COVID-19's symptoms are fatigue, muscle pain, and psychological disorders. The purpose of this study was to describe the occupational characteristics and health conditions of COVID-19 patients who had recovered after being treated at Udayana University Hospital. This study is a descriptive study with a quantitative method and cross-sectional design. The research samples were 110 COVID-19 patients treated at Udayana University Hospital from June to August 2020 and taken using random sampling. The results showed that the highest proportion of respondents were aged between 24-44 years (44.5%), with almost equal proportions of women (50.1%) and men (49.09%). Most of them lived in Denpasar (46.36%). Most respondents work as private sector employees (24.55%), and 70% of them were using personal protective equipment (PPE) while working. Most respondents needed less than seven days to return to work after being declared